2017
DOI: 10.21580/phen.2017.7.1.1491
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Strategi Problem Posing terhadap Critical Literacy Siswa SLB

Abstract: AbstrakTujuan penelitian ini yaitu untuk mengetahui dampak strategi problem posing terhadapcritical literacysiswa sekolah luar biasa (SLB). Subjek Penelitian kualitatif ini menggunakan Single Subject Research Design yaitu satu siswa SLBtipe D(Tunadaksa) kelas VII SLB Purwosari, Kudus. Penelitian ini terdiri atas dua fase yaitu: (1) Fase Baseline "A", observasi atau melakukan pengukuran no intervation pada Prosen belajar mengajar (PBM) oleh guru kelas di dalam kelas integrasi untuk melihat keadaan/perilaku awal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this phase, an introverted student will be given treatment in the form of teaching and learning activities using a problem-based learning model, which will be followed by tests of students' mathematical reasoning abilities after being given treatment. During the intervention phase measurements are carried out on the target behavior continuously until it reaches stable data (Lovaas, 2003), if there is a change in target behavior in the intervention phase after compared with the baseline, it is assumed that the change is due to the influence of the independent variable or intervention (Hartiningsih, 2013;Iswinarti & Cahyasari, 2017;Lovaas, 2003;Rusilowati, Anisa Sholihah, 2017;Sunanto et al, 2005). In general, the design of the study is depicted as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In this phase, an introverted student will be given treatment in the form of teaching and learning activities using a problem-based learning model, which will be followed by tests of students' mathematical reasoning abilities after being given treatment. During the intervention phase measurements are carried out on the target behavior continuously until it reaches stable data (Lovaas, 2003), if there is a change in target behavior in the intervention phase after compared with the baseline, it is assumed that the change is due to the influence of the independent variable or intervention (Hartiningsih, 2013;Iswinarti & Cahyasari, 2017;Lovaas, 2003;Rusilowati, Anisa Sholihah, 2017;Sunanto et al, 2005). In general, the design of the study is depicted as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, the assessment of lectures still focuses on assessing studens' learning outcomes. (Rusilowati, 2017) stated that evaluation is a very important part in the learning process, but it is often ignored by teaching staff. Lecturers need to be encouraged to carry out evaluations not only for their students, but also for themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that need to be evaluated from the subject are (1) lecture design, (2) lecture syllabus, (3) lecture content, (4) lecture materials and (5) lecture method, Matiru, Mwangi & Schettle. (Rusilowati, 2017) Lecture design and syllabus are components to support the routine duties of lecturers in planning. Materials and methods are the supporting components in managing and administering assignments.…”
Section: Introductionmentioning
confidence: 99%